خصائص التصور الفلسفي للقرآن الكريم والوحي النبوي عند منجي لسود في كتابه إسلام الفلاسفة - Makmun, Muhammad; Budiningsih, Dessy Yanti Srie (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study tries to present the characteristics of philosophical knowledge of the Qur'an and Prophetic Revelation according to Munji Laswad in his book Islâm wa al-Falâsifa